Beethoven's sonatas for the pianoforte edited and fingered by W. Dorrell - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Dorrell, W. (William), 1810-1896 (editor):::Contributor:::::::::::: (United Kingdom; Boosey & Co.; London, 2023)
Four of Beethoven's piano sonatas (opp. 22, 26, and 27/2 [as no. 1], and 27/1 [as no. 2]) edited and fingered by William Dorrell and published as no. 48 of "Boosey's Cabinet Classics" in octavo format.